Discovery of 2-(4-Methylfuran-2(5H)-ylidene)malononitrile and Thieno[3,2-b]thiophene-2-carboxylic Acid Derivatives as G Protein-Coupled Receptor 35 (GPR35) Agonists - Deng, Huayun (American Chemical Society, 2011)
[Image: see text] Screening with dynamic mass redistribution (DMR) assays in a native cell line HT-29 led to identification of two novel series of chemical compounds, 2-(4-methylfuran-2(5H)-ylidene)malononitrile and thieno[3,2-b]thiophene-2-carboxylic acid derivatives, as GPR35 agonists. Of these, 2-(3-cyano-5-(3,4-dichlorophenyl)-4,5-dimethylfuran-2(5H)-ylidene)malononitrile (YE120) and 6-bromo-3-methylthieno[3,2-b]thiophene-2-carboxylic acid (YE210) were found to be the two most potent GPR35 agonists with an EC(50) of 32.5 ± 1.7 nM and 63.7 ± 4.1 nM, respectively. Both agonists exhibited better potency than that of zaprinast, a known GPR35 agonist. DMR antagonist assays, knockdown of GPR35 with interference RNA, receptor internalization assays, and Tango β-arrestin translocation assays confirmed that the agonist activity of these ligands is specific to GPR35. The present study provides novel chemical series as a starting point for further investigations of GPR35 biology and pharmacology.